Considerations on the acculturation process in the light of research on Macedonian emigration to the Principality and Kingdom of Bulgaria (a case study) - Pandevska, Maria (Balcanica Posnaniensia. Acta et studia, 2023)
Theorists of migration attempt to establish certain basic frameworks for their classification and ranking, and nowadays, they also do so by introducing subcategories. However, the complexities still burden the precise delineation of all nuances of migration processes and their causes. This article, as a case study, is trying to make a small contribution to the vast topic of Balkan migrations. The focus is solely on the migration processes of the Macedonian population towards the territory of Bulgaria (in the 1870s and at the beginning of the 20th century) and their aftermath (acculturation). For this occasion, starting from the premise of „all refugees are migrants, but not every migrant is a refugee”, migrations are defined only using the following terms: 1) forced migrations with their product being refugees, and 2) continuous voluntary or so-called „quiet” migration processes. This article analyses an original document produced by a marginalised group in Bulgarian society: „ notes” written on the blank spaces of the history. In this case, the viewpoints of these author(s) clash with the mainstream immigration policy of Bulgaria. This document in itself is xenophobic towards all those who do not originate from Bulgaria. However, certain details it provides correspond to the ways in which so-called „quiet” migrations unfold.